Analysis of Formaldehyde Content in Tofu Products as an Indicator of Food Safety in Pidie Regency - Zulfajriana; Arif Sardi; Diannita Harahap (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to identify the presence of formaldehyde in white tofu circulating in Pidie Regency as an indicator of food safety. The research employed a descriptive design with an exploratory approach, using qualitative testing through two techniques: the use of red dragon fruit peel filtrate as a natural indicator in the initial stage and a rapid test kit as a confirmatory method. The samples consisted of 48 white tofu samples collected from 12 sub-districts, with each sub-district represented by four samples obtained from different producers. Sampling was conducted purposively by considering market activity level, number of vendors, and ease of site access. The samples were prepared through a homogenization process prior to testing. The presence of formaldehyde was determined based on color change, reaction time, and color intensity observed during the testing process. The results showed that 12 samples (25%) were positively detected as containing formaldehyde, while the remaining 36 samples (75%) tested negative. Positive samples were generally found in areas with relatively high distribution and trading activity. Based on these findings, it can be concluded that formaldehyde is still present in a proportion of white tofu sold in Pidie Regency. Therefore, enhanced monitoring and education for business actors are needed. In addition, red dragon fruit peel filtrate shows potential as a simple, economical, and environmentally friendly preliminary screening method.